Post-Translational Modification of GPX4 is a Promising Target for Treating Ferroptosis-Related Diseases - Cui, Can; Yang, Fei; Li, Qian (Frontiers in Molecular Biosciences, 2022)
Glutathione peroxidase 4 (GPX4) is one of the most important antioxidant enzymes. As the key regulator of ferroptosis, GPX4 has attracted considerable attention in the fields of cancer, cardiovascular, and neuroscience research in the past ten years. How to regulate GPX4 activity has become a hot topic nowadays. GPX4 protein level is regulated transcriptionally by transcription factor SP2 or Nrf2. GPX4 activity can be upregulated by supplementing intracellular selenium or glutathione, and also be inhibited by ferroptosis inducers such as ML162 and RSL3. These regulatory mechanisms of GPX4 level/activity have already shown a great potential for treating ferroptosis-related diseases in preclinical studies, especially in cancer cells. Until recently, research show that GPX4 can undergo post-translational modifications (PTMs), such as ubiquitination, succination, phosphorylation, and glycosylation. PTMs of GPX4 affect the protein level/activity of GPX4, indicating that modifying these processes can be a potential therapy for treating ferroptosis-related diseases. This article summarizes the protein characteristics, enzyme properties, and PTMs of GPX4. It also provides a hypothetical idea for treating ferroptosis-related diseases by targeting the PTMs of GPX4.